Perancangan Struktur Kontrol Penggilingan Batubara pada Sistem Pembakaran Batubara - Stefanus Yudi Irwan; Awang Noor Indra Wardana; Ester Wijayanti (Universitas Syiah Kuala, 2019)
The inability of the coal mill control structure to monitor and control pulverized coal ﬂow causes operational and environmental problems. The research was done to design the new control structure for coal mill in coal firing system to achieve an improvement on control system performance compared to the existing control structure. Cascade control, blend station, and feedback control was used to control the ﬂow of coal, the ﬂow of primary air, and temperature of the pulverized coal. The result of the evaluation shows that the new control structure capable of fulfilling all the control objectives applied to it. Implementation of the new control structure capable to make the step response of the coal mill to have an average settling time at 161.75 seconds with 0% overshoot. The new control structure also capable to make the pulverized coal fineness at the range of 70% to 75% and moisture content at the range of 2.18% to 2.28%. The result of the evaluation makes the control performance of the new control structure is better than the previous coal mill control structure.